Overall and abdominal obesity and incident aortic valve stenosis: two prospective cohort studies - Larsson, Susanna C. (Eur Heart J, 2017)
AIMS: The aim of this study was to examine the association of overall and abdominal obesity with aortic valve stenosis (AVS) incidence in two prospective cohorts. METHODS AND RESULTS: We used data from the Cohort of Swedish Men and the Swedish Mammography Cohort, involving 71 817 men and women who were free of cardiovascular disease and had reported their anthropometric measures in 1997. Aortic valve stenosis cases were ascertained through linkage with nationwide registers on hospitalization and causes of death. Data were analysed using Cox proportional hazards regression. During a mean follow-up of 15.3 years, 1297 incident AVS cases (771 in men; 526 in women) were ascertained. Both overall and abdominal obesity, measured as body mass index (BMI) and waist circumference, respectively, was associated with AVS incidence, with similar associations in men and women. Compared with BMI 18.5–22.5 kg/m(2), the multivariable hazard ratios were 1.24 (95% confidence interval [CI] 1.05–1.48) for overweight (BMI 25.0–29.9 kg/m(2)) and 1.81 (95% CI 1.47–2.23) for obesity (BMI ≥30 kg/m(2)). The hazard ratio for substantially increased waist circumference (men: ≥102 cm; women: ≥88 cm) compared with normal waist circumference (men: <94 cm; women: <80 cm) was 1.30 (95% CI 1.12–1.51). The proportion of AVS cases estimated to be attributed to overweight and obesity combined (BMI ≥25 kg/m(2)) was 10.8% (95% CI 5.2–16.4%). CONCLUSION: These findings indicate that obesity is associated with an increased risk of AVS and that a large proportion of the cases may be prevented if the population maintained a healthy BMI.